Investigation and evaluation of construction and commissioning risks in construction projects (Case Study: Hospital) - Ibrahim Abdolahnejad; Ahad Nazari; Milad Rahmatinia (مهندسی و مدیریت ساخت)
One of the most important project management areas is project risks management. This area of project management knowledge, give manager the power to improve project performance. Costs overrun, delays and quality defects, in construction project, is the result of the poor project performance. By use project risk management knowledge, important steps can be taken to improve this crucial matter.The goal of this research is survey construction and commissioning of hospital risks. For this purpose, processional attribute of project management body of knowledge is used to evaluate and survey the risks of design to construction and commissioning of hospital. According to the results the top three risks are: incoordination between project participants, delay in bill payment by the government (owner), and main change in executive plans and technical specification. Quantitative evaluation show that, this project take 10 years and the highest risks is belong to the construction of main building and campus. According to the results the top three risks are: incoordination between project participants, delay in bill payment by the government (owner), and main change in executive plans and technical specification. project implementation was simulated by 5000 iterates, result show that, this project take minimum 5 years and maximum 10 years, and by 80percent probability it will finish at 8 years. In term of cost, due to the lack of reliable information the results aren't very reliable, however, with a maximum budget of 140 billion, minimum budget of 70 billion, and average budget of 88 billion, it will be completed.